Computer vision for structural dynamics and health monitoring - Feng, Dongming, 1985-; Feng, Maria, 1961- (Wiley-ASME Press series., 2020)
"This book aims to relay the principles of computer vision/sensing technology and its applications in structural dynamics and health monitoring. The book provides a comprehensive, state-of-the-art review of the collective experience the SHM community has gained in recent years. By extensively exploring the potentials of the vision sensor as a fast and cost-effective tool for solving SHM problems based on both time and frequency domain analytics, this book aims to help broaden the application of emerging computer vision sensor technology in not only scientific research but also engineering practice"--